Hydroxyurea-Induced miRNA Expression in Sickle Cell Disease Patients in Africa - Mnika, Khuthala; Mazandu, Gaston K.; Jonas, Mario; Pule, Gift D.; Chimusa, Emile R.; Hanchard, Neil A.; Wonkam, Ambroise (Frontiers in Genetics, 2019)
Hydroxyurea (HU) is clinically beneficial in Sickle Cell Disease (SCD) through foetal haemoglobin (HbF) induction; however, the mechanism of HU is not yet fully elucidated. Selected miRNAs have been associated with HU-induced HbF production. We have investigated differential HU-induced global miRNA expression in peripheral blood of adult SCD patients in patients from Congo, living in South Africa. We found 22 of 798 miRNAs evaluated that were differentially expressed under HU treatment, with the majority (13/22) being functionally associated with HbF-regulatory genes, including BCL11A (miR-148b-3p, miR-32-5p, miR-340-5p, miR-29c-3p), MYB (miR-105-5p), and KLF-3 (miR-106b-5), and SP1 (miR-29b-3p, miR-625-5p, miR-324-5p, miR-125a-5p, miR-99b-5p, miR-374b-5p, miR-145-5p). The study provides additional miRNA candidates for therapeutic exploration.